2016
DOI: 10.1093/mnras/stw464
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the nature of the QPO and its harmonic in GX 339-4 using frequency-resolved spectroscopy

Abstract: We use frequency-resolved spectroscopy to examine the energy spectra of the prominent low frequency Quasi-Periodic Oscillation (QPO) and its harmonic in GX 339-4. We track the evolution of these spectra as the source makes a transition from a bright low/hard to hard intermediate state.In the hard/intermediate states, the QPO and time averaged spectra are similar and the harmonic is either undetected or similar to the QPO. By contrast, in the softer states, the harmonic is dramatically softer than the QPO spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…In each panel, the blue arrow at the center represents the projection of the corona axis J C on the disk plane. Animated versions of these plots can be viewed at and downloaded from http://202.127.29.4/AGN/beiyou/QPO/index_QPO.html for the observed harmonic in the power spectrum of BHXRB (Axelsson et al 2014;Axelsson & Done 2016;Huang et al2018;de Ruiter et al 2019;Xiao et al 2019;Stevens & Uttley 2016;Stevens et al 2018), which will be further studied in the next paper.…”
Section: The Case Of Lamp-postmentioning
confidence: 99%
“…In each panel, the blue arrow at the center represents the projection of the corona axis J C on the disk plane. Animated versions of these plots can be viewed at and downloaded from http://202.127.29.4/AGN/beiyou/QPO/index_QPO.html for the observed harmonic in the power spectrum of BHXRB (Axelsson et al 2014;Axelsson & Done 2016;Huang et al2018;de Ruiter et al 2019;Xiao et al 2019;Stevens & Uttley 2016;Stevens et al 2018), which will be further studied in the next paper.…”
Section: The Case Of Lamp-postmentioning
confidence: 99%
“…In a recent study, Axelsson & Done (2016), using frequency-resolved spectra suggest further evidence for two major Comptonization regions in BH binaries i.e., a soft one, the origin of which is associated with the disk, and a hard one which is apparently independent of the disk. They further suggest that both are likely to be inhomogeneous.…”
Section: Resultsmentioning
confidence: 94%
“…The second harmonic, in contrast, is significantly softer than the time-averaged spectrum. A similar analysis of GX 339-4 [12] additionally revealed that the rms spectrum of the second harmonic can be described by a low-temperature, optically thick Comptonized component that is not required to be present in the rms spectrum of the fundamental, which instead includes a higher temperature Comptonized component. The authors suggested that these results could be explained by precession of a stratified inner accretion flow, which is hotter closer to the BH.…”
Section: Frequency-resolved Spectroscopymentioning
confidence: 89%
“…We can understand that these two equations have wave-like solutions forl, therefore explaining the name 'wave-like regime', by exploring the invicid (α = 0), Keplerian (Ω φ = Ω r = Ω z ) limit. In this case, equations (11) and (12) can be combined to find…”
Section: The Diffusive and Wave-like Regimesmentioning
confidence: 99%